Gastroesophageal reflux in cystic fibrosis across the age spectrum - Woodley, Frederick W.; Hayes Jr, Don; Kopp, Benjamin T.; Moore-Clingenpeel, Melissa; Machado, Rodrigo Strehl; Nemastil, Christopher J.; Jadcherla, Sudarshan; Di Lorenzo, Carlo; Kaul, Ajay; Mousa, Hayat (Translational Gastroenterology and Hepatology; Vol 4 (September 2019): Translational Gastroenterology and Hepatology, 2019)
Background: Scientific advances have improved longevity in cystic fibrosis (CF) patients and many of these patients can expect to experience age-related gastrointestinal co-morbidities. We aimed to assess the extent to which age might impact gastroesophageal reflux (GER) in patients with CF. Methods: Our esophageal pH-multichannel intraluminal impedance monitoring database was searched for tracings belonging to CF patients ≥2 years old without prior fundoplication and not taking anti-reflux medications immediately prior (within 7 days) and during the study. Tracings were retrospectively analyzed; Impedance and pH variables were evaluated with respect to age and pulmonary function. Results: Twenty-eight patients were enrolled; 16 children (3.1–17.7 years) and 12 adults (18.2–48.9 years). Among pH probe parameters, correlation analysis showed DeMeester score (P=0.011) and number of acid reflux events lasting >5 minutes (P=0.047) to be significantly correlated with age. Age was not significantly correlated with any of the impedance parameters. Age was negatively correlated with baseline impedance (BI) in the distal esophagus (r=−0.424, P=0.023) and BI was negatively correlated with several pH parameters, including reflux index (r=−0.553, P=0.002), number of total acid reflux events (r=−0.576, P=0.001), number of acid reflux events lasting >5 minutes (r=−0.534, P=0.003), and DeMeester score (r=−0.510, P=0.006). Pulmonary function (percent predicted forced expiratory volume in one minute; ppFEV1) was negatively correlated with age (r=−0.494, P=0.0007). The interaction of age and ppFEV1 and any of the reflux parameters, however, was not significant (P>0.05); the strongest evidence for an interaction was found for the number of acid reflux events reaching the proximal esophagus, but this interaction still did not reach statistical significance (P=0.070). Conclusions: In a small cohort, we found evidence that age may be associated with increased acid exposure and that both age and increased acid exposure are associated with reduced BI in the distal esophagus. The negative relationship between pulmonary function and age in our cohort is not related to GER. This pilot study supports the need for esophageal assessment and treatment of GER as standard components of clinical care for an aging CF population.